Endoscopic septoplasty without nasal packing: our technique and outcomes - Sunitha, Narayana; Lohith, Shivappa (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Septoplasty is one of the common procedures performed in otorhinolaryngology practice for treatment of nasal obstruction caused by deviated nasal septum. Septoplasty is traditionally performed using a headlight and nasal speculum. However Endoscopic technique using rigid endoscopes has gained widespread popularity in recent years. Traditionally after correction of septal deviation the mucosal flaps are opposed and held together by some kind of nasal packing to prevent bleeding and septal hematoma. But the nasal pack causes significant morbidity in the post-operative period and also bleeding and pain while pack removal. In the present study we describe our technique of endoscopic septoplasty without nasal packing, in terms of patient comfort and complications. Methods: It was a descriptive study, conducted at Subbaiah institute of medical sciences, Shimoga from January 2017 to December 2020 on 50 subjects and the results were analyzed. Results: All 50 patients included in the study had reduced NOSE scores on the 2nd post-operative day itself. None of the patients had septal hematoma, reduced oxygen saturation or post-op sinusitis. 3 out of 50 patients had minimal bleeding in the post-operative period. 12 out of 50 patients had crusting post operatively on 2nd day but none had at 2 weeks. One patient had synechiae and one patient had residual septal deviation. Conclusions: Endoscopic septoplasty is preferred over conventional septoplasty. Trans septal quilting sutures has less complication rate, good quality of life and can be practiced easily and hence a valid alternative to intranasal packing following septal surgery.